Revisiting the link between systemic risk and competition based on network theory and interbank exposures - Enrique Bátiz-Zuk; José L. Lara-Sánchez (Banco de México, 2021)
This paper examines the link between bank competition measures and risk indicators using quarterly interbank exposures data for all banks in Mexico during 2008Q1-2019Q1. The classical literature focuses on disentangling the link between competition and individual bank solvency risk. In this paper, we take one step forward in analyzing the relationship between competition and systemic risk. We use counterfactual bank-level contagion risk indicators as a proxy of systemic risk to assess their relationship with traditional competition measures. Our main finding indicates a negative relationship between the bank-level Lerner index and systemic risk. This means that an increase in competition is associated with an increase in systemic risk. Additionally, we find that the implementation of regulatory reform during the period studied does not affect this relationship.
Keywords: C23; D40; G21; G28; L14; L16; L22; 330; Bank competition; systemic risk; financial contagion; financial stability; network models